The Association Between Coworker Support and Work-Family Interference: A Test of Work Environment and Burnout as Mediators - Norling, Leo R.; Chopik, William J. (Frontiers in Psychology, 2020)
Coworker support has been hypothesized to enhance work-life outcomes. However, the mechanisms underlying this association are unclear. Two studies examined how coworker support predicted work-life outcomes through positive work environment and burnout. It was hypothesized that coworker support enhances work environment, and that better work environment is associated with less burnout; in turn, reduced burnout would lead to less negative work-life interference. In two large studies of working adults (total N = 5,666), we found support for our model—coworker support predicted work-family outcomes and this association was mediated by more positive work environments and reduced burnout. Study 2 was a short-term lagged confirmation of the model. Results are discussed in the context of efforts to improve workplace climate, reduce turnover, and improve workers’ job satisfaction.